Prediction of laminar-to-turbulent transition in a separated boundary layer subjected to an external acoustic forcing - Kubacki, S.; Rarata, Z.; Dróżdż, A.; Gnatowska, R.; Sokolenko, V.; Elsner, W. (Archives of Mechanics, 2023)
The new Reynolds-averaged Navier–Stokes (RANS)-based method has been developed for taking into account, in an approximate manner, the effect of external acoustic forcing on laminar-to-turbulent transition in a separated boundary layer. Experimental studies [J.W. Kurelek, B.A Tuna, S. Yarusevych, M. Kotsonis, Three-dimensional development of coherent structures in a two-dimensional laminar separation bubble, AIAA Journal, 59, 7, 1–13, 2020] report an increase of the turbulent shear stress within the separated boundary layer under the influence of acoustic forcing. Enhancement of flow disturbances in a reversed flow region was also reported in our experiment. Experimental findings stimulated the development of a reduced-order aero-acoustic strategy. The effect of acoustic forcing was incorporated into the modelling framework of an algebraic intermittency model. The model component was tuned based on our experimental data and validated on reference experiments. The results show the feasibility of the proposed model to simulate flow over a flat plate and the NACA0018 profile.